Systemic lupus erythematosus and Raynaud's phenomenon - Flavia Emilie Heimovski; Juliana A. Simioni; Thelma Larocca Skare (Sociedade Brasileira de Dermatologia, 2015)
Abstract: BACKGROUND: Patients with systemic lupus erythematosus seem to belong to different serological and clinical subgroups of the disease. Genetic background can cause the appearance of these subgroups. OBJECTIVE: To determine whether Brazilian patients who have systemic lupus erythematosus and Raynaud's phenomenon differ from those who do not. METHODS: Retrospective analysis of 373 medical records of systemic lupus erythematosus patients studied for demographic, clinical and serological data. A comparative analysis was performed of individuals with and without RP. RESULTS: There was a positive association between Raynaud's phenomenon and age at diagnosis (p=0.02), presence of anti-Sm (p=0.01) antibodies and anti-RNP (p<0.0001). Furthermore, a negative association was found between Raynaud's phenomenon and hemolysis (p=0.01), serositis (p=0.01), glomerulonephritis (p=0.0004) and IgM aCL (p=0.004) antibodies. CONCLUSION: Raynaud's phenomenon patients appear to belong to a systemic lupus erythematosus subset with a spectrum of clinical manifestations located in a more benign pole of the disease.